Pemeliharaan Arsip Di Sekretariat DPRD Kota Surakarta - Happy Viona Aderika Putri Mulik; Tutik Susilowati; Winarno Winarno (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to find out: (1) what archives are maintained at the Surakarta City DPRD Secretariat, (2) archive maintenance procedures at the Surakarta City DPRD Secretariat, (3) inhibiting factors in the archive maintenance process at the Surakarta City DPRD Secretariat, (4) efforts to overcome factors inhibiting archive maintenance at the Surakarta City DPRD Secretariat. Sources of research data were obtained from informants (Secretary of the Surakarta City DPRD, Head of General Affairs and Finance, Archivist, documents (SK, PERGUB) and observation results. The sampling technique used purposive sampling and snowball sampling. Data collection techniques used interviews, observation and analysis documents. Data validity using triangulation of sources and methods. Data analysis techniques using interactive models. The results of the research show that: (1) the archives maintained at the Surakarta City DPRD Secretariat include two types, namely dynamic archives (active and inactive) and static archives. (2 ) archive maintenance procedures include two stages, namely, (a) maintenance of the archive storage environment, (b) maintenance of the physical condition of archives. (3) inhibiting factors in archive maintenance include: (a) employee negligence, (b) fumigation has not been carried out , (c) the presence of termites. (4) efforts to overcome factors inhibiting archive maintenance include: (a) providing guidance on archive maintenance, (b) equipping facilities and infrastructure to carry out archive maintenance.